2018
DOI: 10.1038/s41598-018-24032-8
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of Multiple Sclerosis using a systems biology approach

Abstract: Multiple sclerosis (MS) is a chronic autoimmune disorder characterized by inflammatory-demyelinating events in the central nervous system. Despite more than 40 years of MS research its aetiology remains unknown. This study aims to identify the most frequently reported and consistently regulated molecules in MS in order to generate molecular interaction networks and thereby leading to the identification of deregulated processes and pathways which could give an insight of the underlying molecular mechanisms of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…Given the association of IL‐3 and IFN levels in the serum, a possible association at the transcriptional level in whole blood cells was explored. An ‘IFN gene signature’ ( EPST11, ISG15, HERC5, IFI44, OAS3, OAS1, LY6E, CMPK2, RSAD2, IFI44L, IFIT1, IFIT3, USP18, SIGLEC1, IFI27, OTOF ) that differentiated most SLE from most healthy donors was determined by hierarchical clustering and pathway analysis of the 500 most variably expressed genes in SLE donors (Figure a), that is those genes that were most differentially expressed in SLE patients compared to healthy donors and were known interferon‐inducible genes per the Interferome database …”
Section: Resultsmentioning
confidence: 99%
“…Given the association of IL‐3 and IFN levels in the serum, a possible association at the transcriptional level in whole blood cells was explored. An ‘IFN gene signature’ ( EPST11, ISG15, HERC5, IFI44, OAS3, OAS1, LY6E, CMPK2, RSAD2, IFI44L, IFIT1, IFIT3, USP18, SIGLEC1, IFI27, OTOF ) that differentiated most SLE from most healthy donors was determined by hierarchical clustering and pathway analysis of the 500 most variably expressed genes in SLE donors (Figure a), that is those genes that were most differentially expressed in SLE patients compared to healthy donors and were known interferon‐inducible genes per the Interferome database …”
Section: Resultsmentioning
confidence: 99%
“…In the top-list of genes with increased expression are several proteins that have shown to play a role in activation of the immune response in MS like EPSTI1 and IFI6. 17,18 In the top-list of genes with reduced expression RPS6KA3 is of interest, as this gene has been shown to be downregulated in blood from MS patients in remission. 19 This study has several drawbacks.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study attempted to concatenate all of the GWAS data and has produced two more restricted gene lists for pwMS versus control and pwMS undergoing treatment. This study identified interferon-gamma signalling as the major pathway involved 47 . Importantly, the multiple genes associated with B-cell function/dysfunction and EBV support a role in MS pathology.…”
Section: Identifying the Genes And Proteins Key To Multiple Sclerosismentioning
confidence: 90%